MEDIA Development of Electronic Student Work Sheet Learning Media (E-LKPD) Web Based Liveworksheet Atmosphere Material Class X.E.4 SHS 3 Painan - Gustina, Adri; Suasti, Yurni; Ernawati, Ernawati (International Journal of Educational Dynamics, 2021)
This study aims to develop geography learning media in the form of electronic student worksheets (E-LKPD) web-based live worksheets on Atmosphere material in class X.E.4 SHS 3 Painan. The method in this study uses research and development, namely the ADDIE development model with five stages including Analysis, Design, Development, Implementation, and Evaluation. The reason for using this development model is because it has a workflow related to the Research and Development (R&D) stage, but makes it easier and more systematic to create a more effective product. One of the causes of students having difficulty understanding the teaching and learning process is due to the unavailability of teaching materials/interactive learning media. This result illustrates that the increase in the initial to the final stage was 14.7% by the expert. The results of developed E-LKPD product obtained the results of a student response questionnaire from 28 students with a final result of 95% with the criteria of "very strong" then the product is declared practical. Web-Based E-LKPD. The Liveworksheet on Atmosphere Material can be used in the teaching and learning process in class and outside the classroom because it is easy to access anytime and anywhere as long as the internet network is active. With the development of E-LKPD learning media, it is hoped that it can be utilized by all parties in increasing interest, learning outcomes, and learning activities in schools.